2024
DOI: 10.1007/s11845-023-03603-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on urinary continence rates after robot-assisted laparoscopic radical prostatectomy

Keith Geraghty,
Kevin Keane,
Niall Davis

Abstract: Objective The objective was to investigate the current evidence and discern urinary continence rates post robot-assisted laparoscopic radical prostatectomy (RALP). Methods A systematic review of the literature was carried out, searching the Embase, Scopus and PubMed databases between 1 January 2000 and 1 May 2020. The search terms “Robotic prostatectomy AND continence” were employed. Articles were selected in accordance with the Preferred Reporting Items f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Surgical treatments for prostate cancer are not free of adverse events. Recent systematic reviews of observational studies have hinted that RARP may result in lower occurrences of urinary incontinence compared to laparoscopic radical prostatectomy (LRP), similar to retropubic radical prostatectomy (RRP), and a higher occurrence compared to brachytherapy (BT) [9]. The ProtecT, which is a randomized controlled trial (RCT) by Barry et al comparing urinary incontinence between RARP and RRP on a nationwide sample of Medicare-age men, showed that 31% had problems with continence, varying from mild to severe stress urinary incontinence (SUI), and 88% had problems with sexual dysfunction.…”
Section: Review Statistics and Previous Studies (Rcts) On Aes Of Rarpmentioning
confidence: 99%
“…Surgical treatments for prostate cancer are not free of adverse events. Recent systematic reviews of observational studies have hinted that RARP may result in lower occurrences of urinary incontinence compared to laparoscopic radical prostatectomy (LRP), similar to retropubic radical prostatectomy (RRP), and a higher occurrence compared to brachytherapy (BT) [9]. The ProtecT, which is a randomized controlled trial (RCT) by Barry et al comparing urinary incontinence between RARP and RRP on a nationwide sample of Medicare-age men, showed that 31% had problems with continence, varying from mild to severe stress urinary incontinence (SUI), and 88% had problems with sexual dysfunction.…”
Section: Review Statistics and Previous Studies (Rcts) On Aes Of Rarpmentioning
confidence: 99%
“…Urinary incontinence (UI) after robot-assisted laparoscopic radical prostatectomy (RALP) is a feared side effect after potentially curative surgical treatment of prostate cancer (PCa) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%